Preconditions of the material choice and inert bodies shapes for drying of liquid foodstuff - Yaroviy, Volodymyr; Yakobchuk, Roman (My University, 2013)
Presented preconditions of the material choice and inert bodies shapes for drying of liquid foodstuff. Наведені передумови вибору матеріалу і форми інертних тіл для сушіння рідких харчових продуктів.
Keywords: inert the body; material and shape; інертні тіла; матеріал і форма; кафедра технологічного обладнання та комп’ютерних технологій проектування